Basic Concepts of Sharia Finance And Practices In Sharia Banking In Indonesia - Havis Aravik; Achmad Irwan Hamzani; Nur Khasanah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
Financing is one of the duties of banking as a financial intermediary institution. Funding is needed to support the smooth running of the business and for planned investments. This study discusses the basic concepts of Islamic financing and the practices of Islamic banking in Indonesia. This research is library research where all the data used comes from library data relevant to the topic under study which comes from books, journals, papers, and other document sources and is verified, interpreted, and analyzed both content and others. The result is that financing is funding provided to certain parties to facilitate investment and has been designed in such a way both for its own sake and the institution. In the practice of Islamic banking in Indonesia, two financing models are very widely used because they are minimal in risk and easy to implement, namely murabaha and mudharabah financing.